Achievement motivation and task performance in collaborative-open, reflective-evaluative learning - Santos, Ma. Gladiola M. (2005)
This experimental research was conducted to determine if the researcher-designed collaborative-open learning and refective-evaluative learning (CORE) strategy, based on the socio-constructivist theory, would improve achievement motivation and produce better task performance among students. The achievement motivation variable consisted of three dimensions, namely, intrinsic interest, self-efficacy beliefs, and self-regulation. The second variable examined was the task performance consisting of the lower-order thinking objective test and the higher-order thinking essay test. With the support of results on focus-group interview with the experimental group, the learner-centered CORE strategy was seen to yield more positive motivational and higher-order thinking outcomes.
"March 2005."
Thesis (Ph.D. Education : Educational Psychology)--University of the Philippines, Diliman.
Keywords: College students -- Philippines -- Psychology; Academic achievement -- Philippines